Eukaryotic ternary transcription complexes: transcription complexes of RNA polymerase II are associated with histone-containing, nucleosome-like particles in vivo. - Sargan, D R (Nucleic Acids Res, 1985)
Using a psoralen crosslinking, radioactive labelling technique, we have previously been able to study ternary transcription complexes containing DNA-dependent RNA polymerases I and II which are released from rat liver nuclei by endogenous nuclease digestion [Sargan and Butterworth, refs 1 and 2]. Although the DNA component of these complexes was found to have a 'nucleosome-like' size profile and although the experimental conditions for autodigestion were designed to minimise histone rearrangement, it is necessary to provide further evidence that the periodicity of nuclease cutting around these transcription complexes is conferred by histones. Studies using secondary nuclease digestion of the released transcription complexes now show a digestion barrier characteristic of that conferred by nucleosomal histones which is lost if histones are removed from the complexes. Furthermore, antibodies raised against histones are effective in precipitating transcription complexes of RNA polymerase II and, to a lesser extent, of RNA polymerase I. The data suggest that, in rat hepatic tissue, transcription complexes are in very close proximity (within a few hundred base pairs) of histone-containing, nucleosome-like particles in vivo. IMAGES: